(untitled) (Damascus University Journal of agriculture sciences, 2025)
This Research was carried out at the laboratories of the Department of Food Sciences – Faculty of Agriculture- University of Damascus and Food biotechnology laboratory at the National Commission for Biotechnology and the laboratories of the Department of Food Engineering Technologies – Faculty of Technological Engineering - University of Aleppo during 2022- 2023. The aim of this Research was to study the chemical, physical and functional properties, extraction and quantification of biologically active compounds in sesame husks By-Products of Tahini Halvah. The results of the chemical Analysis of sesame husks showed a high content in fiber and ash, 35.97, 30.17%, respectively. As for the content of moisture, oil, protein, and NaCl, were 5.07, 8.09, 9.63, and 1.24%, respectively. The results of the physical Analysis showed a decrease in water activity 0.39, while the bulk and Tapped Density were 0.52 and 0.72 g/cm3, respectively. The values of Color Indicators, L, a, b, C, were 48.03, 6.35, 18.81, and 20.59, respectively. The Functional Analysis showed the ability of sesame husks to bind both water and oil. While anti-nutritional Analysis showed a high content of oxalic acid 2.52%, and 1.7% by Phytic acid. The yield of the ethanol extract for sesame husks was 3.26%, and the results showed an increase in the content of this extract in total phenols, and antioxidant activity by the free radical method DPPH. The antioxidant activity of the husks extract was lower than ascorbic acid, with an IC50 value of 39.39 and 6.65 μg/ml, respectively. Sesame husks can be used as a functional ingredient in the manufacture of food rich in dietary fiber, and as a good source of natural antioxidants, thus giving a benefit value that alleviates the environmental and financial problems resulting from the disposal of these husks.